Zastosowanie teorii zarządzania strategicznego w małych przedsiębiorstwach rodzinnych - Sułkowski, Łukasz; Marjański, Andrzej (Implementation of strategic management theory in small family businesses, 2006)
Small family businesses meet problems similar to other small enterprises in the area of strategy creation and implementation. Planner and analytic approach to strategy should be changed into evolutionary and emergent concept. The modification of dominant approach to strategy of small enterprises seems to be inevitable. The new theory should, on the one hand, fulfil the requirement of flexibility, and not restrict the chances of enterprise by strict objectives and mission, but on the other hand, must take into account social factors influencing strategy creation and implementation (i.e. family interests in FB).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 301-306